Conglomeration versus Strategic Focus: Evidence from the Insurance Industry - Berger, Allen N.; Cummins, J.David; Weiss, Mary A.; Zi, Hongmin (Journal of Financial Intermediation, 2000)
We provide evidence on the validity of the it conglomeration hypothesis versus the strategic focus hypothesis for financial institutions using data on U.S. insurance companies. We distinguish between the hypotheses using profit scope economies, which measure the relative efficiency of joint versus specialized production, taking both costs and revenues into account. The results suggest that the conglomeration hypothesis dominates for some types of financial service providers and the strategic focus hypothesis dominates for other types. This may explain the empirical puzzle of why joint producers and specialists both appear to be competitively viable in the long run. Journal of Economic Literature Classification Numbers: G22, G28, G34, L23, L89.